Kazimierz S. Kozlowski, 1928– - Beighton, Peter; Vanhoenacker, Filip M. (Seminars in Musculoskeletal Radiology, 2023)
This history page in the series “Leaders in MSK Radiology” is dedicated to the achievements of the Polish radiologist Kazimierz Kozlowski, whose name is associated with the Kozlowski type of spondylometaphyseal dysplasia.
Keywords: skeletal dysplasia; Autosomal Dominant Spondylometaphyseal Dysplasia, Kozlowski type; history